Español - Villegas, Fulgencio (2020)
In this article we explain the relativistic eects in the Global Positioning System (GPS); Corrections due to Special Relativity and General Relativity are analyzed. Although the gravitational effects are weak and the speeds are small, they nevertheless generate signicant relativistic efects. If these eects are not taken into account, errors would occur in the measurement of time and in the position of the GPS device (in the order of 11.5 km).